Anaesthetic Management of a Case of Pheochromocytoma - Panta, Sunita; Rai, Shashi; KC, Nagendra Bahadur (Medical Journal of Shree Birendra Hospital, 2010)
Pheochromocytoma is rare, accounting for less than 0.1 % of hypertensive population. In this report, we describe a 40-year-old male a diagnosed case of pheochromocytoma who underwent adrenalectomy under general anaesthesia with epidural analgesia. The patient was adequately prepared with alpha adrenergic blockers. Intraoperative course was stormy but was managed with antihypertensives, inotropes and intravenous fluid. The patient was electively ventilated overnight and had an uncomplicated recovery. Pheochromocytoma is a rare medical condition and an anaesthesiologist comes across it only a few times in his or her practice. Therefore there is a limited exposure in management. Furthermore hemodynamic instability encountered intra and postoperatively itself is a challenge. Hence management of a case of pheochromocytoma demands a meticulous preoperative preparation, advanced monitoring devices and good interdepartment coordination preferably in a tertiary medical center for a favourable outcome. Key words: Haemodynamic instability; inotropes; pheochromocytoma; Sodium Nitroprusside. DOI: 10.3126/mjsbh.v9i1.3486 Medical Journal of Shree Birendra Hospital Vol.9(1) 2010 19-23